Bioactive Molecules with Healthy Features to Food and Non-food Applications - Torres, María Dolores; Falqué López, Elena (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The main aim of this Special Issue is to provide an overview of recent advances in the processing, characterization, structure-activity links, and applications of natural bioactive molecules from a wide range of sources. The incorporation of these bioactive compounds in innovative functional matrices is also a matter of interest.